Akad Sukuk Ijarah dan Ijarah Muntahiyah Bittamlik, Praktiknya di Indonesia dan Bagaimana di Negara Dubai (Lembaga Pengembangan Kinerja Dosen, 2025)
The Islamic financial market, especially sukuk instruments, has experienced rapid development globally as an alternative financing that is in accordance with sharia principles. Sukuk, especially sukuk ijarah, functions as a certificate of asset ownership that allows investors to obtain a share in the ownership of assets and profits from the results of their activities without violating the principles of usury and gharar. In the context of Indonesia and Dubai, the development of sukuk is supported by a strong legal framework, regulations, and adequate supervisory institutions. Dubai has leveraged the strength of its infrastructure and reputation as an international Islamic financial center to strengthen the asset-based sukuk ijarah market, while Indonesia shows great potential in developing sukuk as an instrument of national economic development. However, challenges such as limited assets, fluctuations in the value of underlying assets, and the need for harmonization of international standards must still be overcome to strengthen and expand the sukuk market globally and sustainably. Optimal development of sukuk ijarah is expected to support stable and inclusive sharia economic growth in the future.